Front Cover. Issue 1 (21st December 2020) - Geniez, Philippe; Cheylan, Marc; Crochet, Pierre‐André
Abstract : The cover image relates to the Research https://onlinelibrary.wiley.com/doi/10.1111/ddi.13176 Malpolon monspessulanus Locations are both 'Occitanie region, France' and the photos were both taken in 2020. The Photography credit : Maxime Briola, Regards du Vivant.